The impact of local health professions education grants: is it worth the investment? - Humphrey-Murto, Susan; Walker, Kyle; Aggarwal, Simran; Preet Kaur Dhillon, Nina; Rauscher, Scott; Wood, Timothy J. (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Background: Local grants programs are important since funding for medical education research is limited. Understanding which factors predict successful outcomes is highly relevant to administrators. The purpose of this project was to identify factors that contribute to the publication of local medical education grants in a Canadian context.Methods: Surveys were distributed to previous Department of Innovation in Medical Education (DIME) and Department of Medicine (DOM) grant recipients (n = 115) to gather information pertaining to PI demographics and research outcomes. A backward logistic regression was used to determine the effects several variables on publication success. Results: The overall publication rate was 64/115 (56%). Due to missing data, 91 grants were included in the logistic regression. Variables associated with a higher rate of publication; cross departmental compared to single department OR = 2.82 (p = 0.04), being presented OR = 3.30 (p = 0.01), and multiple grant acquisition OR = 3.85 (p = 0.005) Conclusion: Although preliminary, our data suggest that increasing research publications from local grants may be facilitated by pooling funds across departments, making research presentations mandatory, and allowing successful researchers to re-apply.